Disagreement strategies in the online comments of The Malaysian Insider / Azimah Zainudin - Azimah, Zainudin (2017)
This study aims to investigate the disagreement strategies and ways to mitigate disagreement in The Malaysian Insider‟s comments. This study is limited to the topic of disagreement and mitigating disagreement in an online news portal, The Malaysian Insider (TMI). For the purpose of this study, Shum and Lee‟s disagreement strategies (2013) and Locher‟s mitigating strategies (2004) were used as the framework. The qualitative method was employed in this study. The findings showed that disagreements were expressed by giving an opposite opinion, raising a rhetorical question, giving a negative comment, making a personal stance, reprimanding, making an ironic statement, rewording and the use of insulting words. The analysis showed that hedges, shifting responsibility, modal auxiliaries, but, giving personal or emotional reasons and token agreement were employed to mitigate disagreement